Morphometric and molecular analyses of Tylodelphys sp. metacercariae (Digenea: Diplostomidae) from the vitreous humour of four fish species from Lake Naivasha, Kenya. Issue 4 (July 2015) - Otachi, E.O.; Locke, S.A.; Jirsa, F.; Fellner-Frank, C.; Marcogliese, D.J.
Abstract Even in the relatively well-characterized faunas of the developed world, it is difficult to discriminate species of metacercariae in the Diplostomidae using morphology, infection site or host use. The taxonomy, diversity and ecology of diplostomids infecting freshwater fishes in the African continent are particularly poorly known, but recent morphometric and genetic studies have revealed four species of diplostomids in the eyes and brains of siluriform fishes. In the present study, diplostomid metacercariae were collected from the eyes of 288 fish comprising two species within the Cyprinidae (Cyprinus carpio, n= 145, and Barbus paludinosus, n= 67), two Cichlidae (Oreochromis leucostictus, n= 56, and Tilapia zillii, n= 18) and one Centrarchidae (Micropterus salmoides, n= 2) caught in Lake Naivasha, Kenya. Morphometric (14 characters and 8 indices in 111 specimens) and molecular (sequences from the barcode region of the cytochrome c oxidase 1 gene in 11 specimens) data were used to discriminate species. All fish species except B. paludinosus were infected with Tylodelphys metacercariae that were initially separated into two types differing mainly in body length. However, this morphological distinction received only intermediate support in quantitative morphological analysis and molecular data indicated that both morphotypes were conspecific. All the specimens therefore are inferred to belong to a single unidentified species of Tylodelphys, which is not conspecific with any other diplostomid for which comparable molecular data are available, including four diplostomid species known from siluriform fish in Nigeria and Tanzania.